Here, There, and Everywhere: The Ubiquitous Distribution of the Immunosignaling Molecule Lysophosphatidylcholine and Its Role on Chagas Disease - Silva-Neto, Mário Alberto C.; Lopes, Angela H.; Atella, Georgia C. (Frontiers in Immunology, 2016)
Chagas disease is a severe illness, which can lead to death if the patients are not promptly treated. The disease is caused by the protozoan parasite Trypanosoma cruzi, which is mostly transmitted by a triatomine insect vector. There are 8-10 million people infected with T. cruzi in the world, but the vector-borne transmission occurs only in the Americas, especially Latin America. About 30 % of chronically infected people develop cardiac diseases and up to 10 % develop digestive, neurological or mixed disorders. Lysophosphatydilcholine (LPC) is the major phospholipid component of oxidized low-density lipoproteins associated with atherosclerosis-related tissue damage. Insect-derived LPC is a powerful chemoattractant for inflammatory cells at the site of the insect bite, enhances parasite invasion, and inhibits the production of nitric oxide (NO) by T. cruzi-stimulated macrophages. The recognition of the ubiquitous presence of LPC on the vector saliva, its production by the parasite itself and its presence both on patient plasma as well as its role on diverse host x parasite interaction systems lead us to compare its distribution in nature with the title of the famous Beatles song “Here, There and Everywhere” recorded exactly 50 years ago in 1966. Here, we review the major findings pointing out the role of such molecule as an immunosignaling modulator of Chagas disease transmission. Also, we believe that future investigation of the connection of this ubiquity and the immune role of such molecule may lead in the future to novel methods to control parasite transmission, infection and pathogenesis.